Describing Pregnant Women's Anxiety in Facing Childbirth Based on the Maternal Age - Wibowo, Wasis Purwo; Bawono, Yudho (Procedia of Social Sciences and Humanities, 2024)
The pregnancy process causes pregnant women to experience physiological and psychological changes during pregnancy, which make them uncomfortable and experience emotional changes. There are many problems that pregnant women may face, including dealing with the birthing process and anxiety during pregnancy. This anxiety is influenced by several factors, one of which is the maternal age. The aim of this research is to analyze differences in anxiety of pregnant women in facing childbirth based on the maternal age. The research method used in this research is descriptive-quantitative. The research sample consisted of pregnant women who had their pregnancy checked at RSIA dr. Hikmah Sawi Bangkalan. The total sample for this study was 50 pregnant women. Data collection on the anxiety variable facing childbirth used the PASS scale (Perinatal Anxiety Screening Scale). Data were analyzed using the one-way Anova test to determine differences in pregnant women's anxiety about facing childbirth in terms of maternal age. The results of the research show that there is a significant difference between maternal age and pregnant women's anxiety about facing childbirth.